2014
DOI: 10.1007/s12010-014-0953-8
|View full text |Cite
|
Sign up to set email alerts
|

Extractive Fermentation of Xylanase from Aspergillus tamarii URM 4634 in a Bioreactor

Abstract: Of the many reported applications for xylanase, its use as a food supplement has played an important role for monogastric animals, because it can improve the utilisation of nutrients. The aim of this work was to produce xylanase by extractive fermentation in an aqueous two-phase system using Aspergillus tamarii URM 4634, increasing the scale of production in a bioreactor, partially characterising the xylanase and evaluating its influence on monogastric digestion in vitro. Through extractive fermentation in a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Typically, this species is associated with plant biomass degradation as a spoilage fungus, with reports of isolation from food and feed products (Rodrigues et al, 2011 ; Midorikawa et al, 2014 ; Martins et al, 2017 ; Prencipe et al, 2018 ). Previous studies have also highlighted the potential in this species in depolymerization of xylan, through secretion of β-1,4-endoxylanases (Gouda and Abdel-Naby, 2002 ; da Silva et al, 2014 ). Efficient secretion of such xylanases has also been reported in the strain A. tamarii BLU37 (Duarte et al, 2012 ; Monclaro et al, 2016 ).…”
Section: Discussionmentioning
confidence: 83%
“…Typically, this species is associated with plant biomass degradation as a spoilage fungus, with reports of isolation from food and feed products (Rodrigues et al, 2011 ; Midorikawa et al, 2014 ; Martins et al, 2017 ; Prencipe et al, 2018 ). Previous studies have also highlighted the potential in this species in depolymerization of xylan, through secretion of β-1,4-endoxylanases (Gouda and Abdel-Naby, 2002 ; da Silva et al, 2014 ). Efficient secretion of such xylanases has also been reported in the strain A. tamarii BLU37 (Duarte et al, 2012 ; Monclaro et al, 2016 ).…”
Section: Discussionmentioning
confidence: 83%
“…These systems are traditionally used for protein separation and can be applied to the separation of other biological products, such as low molecular weight compounds, organelles, and other macromolecules [97]. In the case of extractive fermentation, ATPS have been applied as extractive fermentation systems for different molecules, such as alkaline phosphatase [98], clavulanic acid [99], lipase [21], and xylanase [100].…”
Section: Techniques Used In Isprmentioning
confidence: 99%
“…On the other hand, lipase production did not follow this profile. Other studies have shown a negative effect of the PEG concentration on enzyme production [10,100,101].…”
Section: Techniques Used In Isprmentioning
confidence: 99%
“…Extractive fermentation in ATPS, a schematic setup of which is illustrated in Figure , is a process that integrates an extraction step in the first processing stage to allow for simultaneous product synthesis and removal. This can ensure the primary recovery and increase productivity by minimizing final product inhibition during fermentation . As suggested by the name, the microbial system is cultured in one of the two phases, while the target biomolecule is excreted and partitioned in the other phase.…”
Section: Introductionmentioning
confidence: 99%
“…This can ensure the primary recovery and increase productivity by minimizing final product inhibition during fermentation. 17 As suggested by the name, the microbial system is cultured in one of the two phases, while the target biomolecule is excreted and partitioned in the other phase. Such a system enables quick recovery of product without the need of harvesting biomass or cell disruption.…”
Section: Introductionmentioning
confidence: 99%